(3GdJhGRf Hjf GdSdWJjf GdJfajPjI hGdJJTQjYjI aj GdfXGe GdHQdeGfj (B: s (3OQGSI ebGQfI eY GdJWHjb Ydi GdfXGe GdOSJhQj GdchjJj (B/ s - (3HOQ eMeO MSf GdLYjOi s; (3eMeO eMeO HOQGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3YdGbI GdSdWI GdJfajPjI HGdSdWI GdJTQjYjI JJCKQ HYhGed ef CgegG UhQI GdfXGe GdSjGSi hdG JJhba GdYdGbI Hjf GdSdWJjf ai Xd GdfXGe GdHQdeGfi Ydi eLQO eGjSei ai Gdabg HhSGFd GdQbGHI GdeJHGOdI aMSH Hd JhLO CjVG LhGfH CNQi dJdc GdYdGbGJ JJeKd ai GdJOGNd hGdJcGed HjfgeG ai eLGdGJ eYjfI hGdJYGhf hGdJhGRf ai eLGdGJ CNQi (B. (3aGdYdGbI Hjf GdSdWGJ ai GdfXGe GdOSJhQi GdchjJi EfeG JJe ai MOhO GdeHOC GdPi bQQJg GdeGOI (B50 (3ef GdOSJhQ MjK JfU gPg GdeGOI Ydi Cfg (B" (3jbhe fXGe GdMce Ydi CSGS aUd GdSdWGJ eY JYGhfgG habG dCMcGe GdOSJhQ(B"s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B403 - 434.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdSdWI GdJTQjYjIs; (3GdSdWI GdJfajPjI s; (3GdHQdeGfs; (3GdJahjV GdJTQjYjs; (3GdMRH GdMGces; (3GdaUd Hjf GdSdWGJs; (3dLGf GdJMbjb GdHQdeGfjIs; (3GbJQGM GdbhGfjfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes